The anticipation of ecopoetics in Muriel Rukeyser's The Life of Poetry. Issue 7 (9th August 2018) - Parks, Cecily
ABSTRACT: The inclusion of excerpts from Muriel Rukeyser's long poem 'The Book of the Dead' (1938) in the 'Historical' section of The Ecopoetry Anthology (2013) testifies to the eco-ethical prescience of Rukeyser's poem, which links working class and racial oppression to environmental damage, and demonstrates how poetry can be held responsible for social and environmental justice. However, Rukeyser's eco-ethical concerns in her work after 'The Book of the Dead' have been largely neglected by literary ecocriticism. This paper proposes that The Life of Poetry (1949) deserves a foundational place in what we now, after the rise of environmental activism in the 1960s, call ecopoetics. In Rukeyser's literary-activist essays, the rhetorical use of natural world imagery to illuminate poetry's ability to effect social and political change reinforces an environmental context for poetic responsibility. Furthermore, Rukeyser's argument for the treatment of poetry as a 'resource' anticipates contemporary environmental discourse on consumption and sustainability and situates poetry squarely within it.